Intracerebral Hemorrhage-Induced Cognitive Impairment in Rats Is Associated With Brain Atrophy, Hypometabolism, and Network Dysconnectivity - Puy, Laurent; Leboullenger, Clémence; Auger, Florent; Bordet, Régis; Cordonnier, Charlotte; Bérézowski, Vincent (Frontiers in Neuroscience, 2022)
The mechanisms underlying intracerebral haemorrhage (ICH)-related cognitive impairment (CI) remain unclear. Long-term structural and functional changes were investigated in the brains of healthy male and female Wistar rats after experimental ICH. Following double injection of autologous blood, rats underwent short-term (onset, 3 and 7 days) and long-term (3 and 6 months) radiological assessment and behavioral tests exploring spontaneous locomotion, anxiety-like behavior and working memory, spatial recognition memory and visual recognition memory. Volumetric and metabolic changes in brain areas were examined by 7Tesla-MRI and [18F] FDG-PET respectively. Brain connectomic disorders and maladaptive processes were seeked through brain metabolic connectivity analysis and atrophy-related network analysis. From an initial hematoma mean volume of 23.35 ± 9.50 mm3, we found early spontaneous locomotor recovery and significant spontaneous blood resorption (≈ 40% of the initial lesion) from day 0 to day 7. After 3 and 6 months, ICH rats exhibited CI in several domains as compared to the sham group (working memory: 58.1±1.2 vs 70.7±1.2 %, p< 0.001; spatial recognition memory: 48.7±1.9 vs 64±1.8 %, p< 0.001 and visual recognition memory: 0.14± 0.05 vs 0.33± 0.04, p= 0.013, in female only). Rats that experienced ICH had remote and concomitant cerebral atrophy and hypometabolism of ipsilateral striatum, thalamus, limbic system and cortical areas (temporal and parietal lobes). Interestingly, both structural and metabolic deterioration was found in the limbic system connected to the affected site, but remotely from the initial insult. On the other hand, increased activity and functional connectivity occurred in the contralateral hemisphere. These connectomics results showed that both maladaptative and compensation processes coexist in the rat brain following ICH, even at young age and in a disease-free setting. These radiological findings deepen our understanding of ICH-related CI and may serve as biomarkers in the view of future therapeutic intervention.